Membangun Positive Brand Image dari Koperasi Sugih Makmur - Christiana, Audi Christiana; Setyadi, Elizabeth Venny; Purnomo, Rafelle; Setiadi, Raymond; Hidayat, Rafi; Heriyanto, Kevin Heriyanto; Asbi, Muhammad; Iswaldi, Ihsan (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
As a plenary citizen, the development of humanity is an obligation to every human being. To accomplish our duty to serve the community in the region of Cianjur especially Ciputri Village Sarongge, we as writer did a “live in” program for a month from the 17th of January till the 14th of February 2019. This article is composed to report the potential, problems, and progress of our partner’s business during this year’s community development program. As Builder 023, we were assigned to help develop our partner’s existing business “Koperasi Sugih Makmur” in terms of finance, marketing, and human resource management to minimalize human error risks in the future such as bad cash flow. We also saw an opportunity for another potential business line, henceforth we decided to develop strawberry jam as a new line of product. Existed since 28th February 2019, this new line of product has already gained improvements such as packaging, operational standards, and sales channels.